The efficacy of internet-delivered treatment for generalized anxiety disorder: A systematic review and meta-analysis - RICHARDS, DEREK; TIMULAK, LADISLAV (My University, 2015)
Generalized Anxiety Disorder (GAD) is typically considered a chronic condition characterized by excessive worry. Lifetime prevalence is 4.3–5.9%, yet only a small percentage seeks treatment. GAD is treatable and in recent years internet-delivered treatment interventions have shown promise. This paper aims to systematically search for literature on internet-delivered psychological interventions for the treatment of GAD and conduct a meta-analysis to examine their efficacy. The purpose of the paper is to inform the community of researchers, program developers and practitioners in internet delivered interventions of the current state-of-the-art and research gaps that require attention. A systematic search of the literature was conducted to find all studies of internet-delivered treatments for GAD (N = 20). Using Review Manager 5 all Randomized Controlled Trials (RCTs; n = 11) that met our established eligibility criteria were included into a meta-analysis that calculated effect sizes via the standardized mean difference. Compared to the waiting-list controls, the results demonstrate positive outcomes for GAD symptoms (d = − 0.91) and its central construct of pathological worry (d = − 0.74). The meta-analysis supports the efficacy of internet-delivered treatments for GAD including the use of disorder-specific (4 studies) and transdiagnostic treatment protocols (7 studies). Caution is advised regarding the results as the data is limited and highly heterogeneous, but revealing of what future research might be needed.
Keywords: Generalized anxiety disorder; Anxiety; Internet interventions; Efficacy; Meta-analysis; Systematic review; Generalized anxiety disorder; Anxiety; Internet interventions; Efficacy; Meta-analysis; Systematic review